Characterization and significance of delayed processing of the feline leukemia virus FeLV-FAIDS envelope glycoprotein. - Poss, M L (1990)
FeLV-FAIDS, an immunodeficiency-inducing isolate of feline leukemia virus, is composed of a pathogenic but replication-defective genome (molecular clone 61C) and a replication-competent but non-immunodeficiency-inducing variant genome (molecular clone 61E). The chimeric virus EECC, composed of the 5' gag-pol of 61E fused to the env-3' LTR of 61C, also induces immunodeficiency. The 61C (or EECC) gp80 can be distinguished from that of 61E on the basis of antigenic recognition, size, and rate of posttranslational processing. We found that the nascent precursor polypeptides of the two viruses were the same size; however, the 61E gp80 rapidly shifted to a smaller size and was subsequently cleaved to gp70, whereas EECC gp80 maintained its nascent size and was cleaved to gp70 only after a prolonged time. Endo-beta-N-acetyl glucosaminidase H and N-glycanase digestions of newly formed glycoproteins resulted in a similar banding pattern for both viruses, indicating that both contained the same number of oligosaccharide side chains and that all of these were high mannose sugars. The metabolic inhibitors of glycosylation, castanospermine or N-methyldeoxynojirimycin, prevented both the rapid trimming of 61E gp80 and its cleavage to gp70. Treatment with mannosidase inhibitors, however, did not affect 61E gp80 processing or size, suggesting that retention of glucose residues on EECC was responsible for these distinguishing properties of the glycoprotein. The pathological consequence of aberrant viral glycoprotein processing was evaluated in feline 3201 T lymphocytes, which are infectable by both 61E and EECC but are killed only by EECC. As in fibroblasts, the EECC glycoprotein produced in lymphocytes was larger, antigenically distinct, and processed more slowly than was the glycoprotein of 61E. Castanospermine treatment of 61E-infected 3201 T cells, however, not only abrogated the antigenic differences between the 61E and EECC glycoproteins but also resulted in a cytopathic effect. Our results suggest that (i) intracellular accumulation of EECC envelope glycoprotein may occur consequent to retention of glucose residues on carbohydrate side chains and (ii) a strong correlation exists between delayed glycoprotein processing and cytopathicity in FeLV-FAIDS-infected T lymphocytes.